Prevalence of clopidogrel non-responders among patients with stable angina pectoris scheduled for elective coronary stent placement - Müller, Iris; Besta, Felicitas; Schulz, Christian; Massberg, Steffen; Schönig, Albert; Gawaz, Meinrad (Thrombosis and Haemostasis, 2003)
Dual antiplatelet therapy with aspirin and clopidogrel decreases the rate of stent thrombosis in patients undergoing percutaneous coronary intervention (PCI). However, despite intensified antiplatelet treatment, up to 4.7% of the patients undergoing coronary stenting develop thrombotic stent occlusion, suggesting incomplete platelet inhibition due to clopidogrel resistance. We evaluated the percentage of clopidogrel nonresponders among 105 patients with coronary artery disease (CAD) undergoing elective PCI. All patients were treated regularly with aspirin 100 mg/d and received a loading dose of 600 mg clopidogrel followed by a maintenance dose of 75 mg/d before PCI. Clopidogrel non-responders were defined by an inhibition of ADP (5 and 20 μMol/L) induced platelet aggregation that was less than 10% when compared to baseline values 4 h after clopidogrel intake. Semi-responders were identified by an inhibition of 10 to 29%. Patients with an inhibition over 30% were regarded as responders. We found that 5 (ADP 5 μMol/L) to 11% (ADP 20 μMol/L) of the patients were non-responders and 9 to 26% were semi-responders. Among the group of nonresponders there were two incidents of subacute stent thrombosis after PCI. We conclude that a subgroup of patients undergoing PCI does not adequately respond to clopidogrel, which may correspond to the occurrence of thromboischemic complications. Point-of-care testing may help to identify these patients who may then benefit from an alternative antiplatelet therapy.
Keywords: Platelets; clopidogrel; non-responders; stenting; coronary artery disease